Pembelajaran Inquiry Melalui Bahan Alam Untuk Mengembangkan Sains Anak Usia Dini di Taman Kanak-Kanak Islam Raudhatul Jannah Payakumbuh - Anastasyia, Raudathul; Suryana, Dadan (Jurnal Family Education, 2022)
One form of learning model is the inquiry learning model. Inquiry learning is a series of learning activities in the form of a critical and analytical thinking process to seek and find the answer to a question in question. This study aims to describe inquiry learning through natural materials to develop science in early childhood at Raudhatul Jannah Islamic Kindergarten Payakumbuh. The type of research that researchers use is descriptive using qualitative methods. In this study, the data collection methods used were observation, interviews and documentation. The results of this study indicate that during the inquiry learning process through natural materials to develop science in children, teachers have used various learning methods for children such as questions and answers, lectures in the form of giving advice, and experiments with forms of learning that allow children to solve the problems they face. By thinking critically and scientifically by using natural materials media that have been designed by the teacher to be very interesting for developing science in earlychildhood